Solutions manual for organic chemistry - Fessenden, Ralph J (Brooks/Cole, 1994)
This solutions manual contains the answers to the essays problems and the end-of chepter problems in fessenden and fessenden,organic chemistry.Also includes is an appendix dealing with nomenclature of organic commpounds.